Aortic Valve Fibroelastoma Masquerading as Transient Ischaemic Attack - Penelope-Anne Gowland; Ragheb Hasan (Case Reports in Cardiology)
The following paper is on a 49-year-old man who presented to accident and emergency department having experienced five hours of left-sided chest pain, tightness in the chest, and shortness of breath. He also reported paresthesia and an ache in the left arm. Further investigations revealed an aortic valve papillary fibroelastoma. Although histologically papillary fibroelastomas are described as benign, they carry with them considerable risk of morbidity and mortality. This patient experienced recurrent transient ischemic attacks (TIAs’). He was taken to theatre on urgent basis to remove the papillary fibroelastoma. His aortic valve was preserved during the operation. The patient had an uneventful recovery following the surgery. His neurologic symptoms resolved following the operation. The operation was curative and no further symptoms were reported at followup.